The current condition and development of the innovative sector of small and medium enterprises (SMEs) in AP Vojvodina - Simin Marina (University Business Academy - Faculty of Economics and Engineering Management, Novi Sad, Serbia, 2021)
Innovation is a fundamental factor of technological progress, economic growth, development and prosperity around the world. Continuous improvement of innovation is the focal part in the development policy of the world's leading countries and presents the key element of the development strategy of the EU - Europe 2020. The economy of AP Vojvodina is still characterized by a low level of innovation. The consequences of a company's insufficient care for technological development based on its own innovative work is a very small number of protected innovations, especially patents and petty patents in our country. The subject of this paper is the research into the current state and number of innovative small and medium enterprises (SMEs) that started business on the basis of their innovation, especially patent or petty patent in AP Vojvodina. The main goal of the paper is to increase the number of innovative SMEs in AP Vojvodina based on the results of this research and proposed measures aimed at creating higher added value, successful market verification of innovations and better market positioning.